COVID-19 in Female and Male Athletes: Symptoms, Clinical Findings, Outcome, and Prolonged Exercise Intolerance—A Prospective, Observational, Multicenter Cohort Study (CoSmo-S) - Widmann, Manuel; Gaidai, Roman; Schubert, Isabel; Grummt, Maximilian; Bensen, Lieselotte; Kerling, Arno; Quermann, Anne; Zacher, Jonas; Vollrath, Shirin; Bizjak, Daniel Alexander; Beckendorf, Claudia; Egger, Florian; et al. (Sports Medicine)
Abstract Background An infection with SARS-CoV-2 can lead to a variety of symptoms and complications, which can impair athletic activity. Objective We aimed to assess the clinical symptom patterns, diagnostic findings, and the extent of impairment in sport practice in a large cohort of athletes infected with SARS-CoV-2, both initially after infection and at follow-up. Additionally, we investigated whether baseline factors that may contribute to reduced exercise tolerance at follow-up can be identified. Methods In this prospective, observational, multicenter study, we recruited German COVID elite-athletes (cEAs, n = 444) and COVID non-elite athletes (cNEAs, n = 481) who tested positive for SARS-CoV-2 by PCR (polymerase chain reaction test). Athletes from the federal squad with no evidence of SARS-CoV-2 infection served as healthy controls (EAcon, n = 501). Questionnaires were used to assess load and duration of infectious symptoms, other complaints, exercise tolerance, and duration of training interruption at baseline and at follow-up 6 months after baseline. Diagnostic tests conducted at baseline included resting and exercise electrocardiogram (ECG), echocardiography, spirometry, and blood analyses. Results Most acute and infection-related symptoms and other complaints were more prevalent in cNEA than in cEAs. Compared to cEAs, EAcon had a low symptom load. In cNEAs, female athletes had a higher prevalence of complaints such as palpitations, dizziness, chest pain, myalgia, sleeping disturbances, mood swings, and concentration problems compared to male athletes ( p < 0.05). Until follow-up, leading symptoms were drop in performance, concentration problems, and dyspnea on exertion. Female athletes had significantly higher prevalence for symptoms until follow-up compared to male. Pathological findings in ECG, echocardiography, and spirometry, attributed to SARS-CoV-2 infection, were rare in infected athletes. Most athletes reported a training interruption between 2 and 4 weeks (cNEAs: 52.9%, cEAs: 52.4%), while more cNEAs (27.1%) compared to cEAs (5.1%) had a training interruption lasting more than 4 weeks ( p < 0.001). At follow-up, 13.8% of cNEAs and 9.9% of cEAs ( p = 0.24) reported their current exercise tolerance to be under 70% compared to pre-infection state. A persistent loss of exercise tolerance at follow-up was associated with persistent complaints at baseline, female sex, a longer break in training, and age > 38 years. Periodical dichotomization of the data set showed a higher prevalence of infectious symptoms such as cough, sore throat, and coryza in the second phase of the pandemic, while a number of neuropsychiatric symptoms as well as dyspnea on exertion were less frequent in this period. Conclusions Compared to recreational athletes, elite athletes seem to be at lower risk of being or remaining symptomatic after SARS-CoV-2 infection. It remains to be determined whether persistent complaints after SARS-CoV-2 infection without evidence of accompanying organ damage may have a negative impact on further health and career in athletes. Identifying risk factors for an extended recovery period such as female sex and ongoing neuropsychological symptoms could help to identify athletes, who may require a more cautious approach to rebuilding their training regimen. Trial Registration Number DRKS00023717; 06.15.2021—retrospectively registered.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

The Mode of Endurance Exercise Influences Changes in EEG Resting State Graphs among High-Level Cross-Country Skiers - Büchel, Daniel; Torvik, Per Øyvind; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Medicine & Science in Sports & Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Cortical thickness and neurocognitive performance in former high‐level female soccer and non‐contact sport athletes - Haase, Franziska Katharina; Prien, Annika; Douw, Linda; Feddermann‐Demont, Nina; Junge, Astrid; Reinsberger, Claus (Scandinavian Journal of Medicine & Science in Sports)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Weaker Quadriceps Corticomuscular Coherence in Individuals Following ACL Reconstruction during Force Tracing - Sherman, David A.; Baumeister, Jochen; Stock, Matt S.; Murray, Amanda M.; Bazett-Jones, David M.; Norte, Grant E. (Medicine & Science in Sports & Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Training matters: Heading incidence and characteristics in children's and youth football (soccer) players - Reeschke, Rebecca; Haase, Franziska Katharina; Dautzenberg, Lena; Krutsch, Werner; Reinsberger, Claus (Scandinavian Journal of Medicine & Science in Sports)
Abstract Objective Concerns about short‐ and long‐term consequences of repetitive heading contributed to heading restrictions in youth football in some countries. This prospective longitudinal cohort study aims to describe heading exposure in children's and youth football over two seasons using standardized video analysis. Methods All matches and training sessions of a male Under‐11 ( n = 29), Under‐15 ( n = 28), Under‐19 ( n = 38), and female Under‐17 ( n = 39) team were videotaped during the seasons 2019–2020 and 2020–2021. Heading frequencies and characteristics were analyzed. Individual heading exposure is presented as average incidence rates (IR) per 1000 match/training hours. Results In 275 matches and 673 training sessions, 22 921 headers were observed. Heading IR per player in matches was 1256 (Under‐11 m), 1608 (Under‐15 m), 1050 (Under‐17 f), and 1966 (Under‐19 m). In training sessions, IR per player was 739 (Under‐11 m), 2206 (Under‐15 m), 1661 (Under‐17 f), and 1419 (Under‐19 m). Five Under‐15 males headed the ball five to eight times per training on average. Most headers were performed without heading duels. Flight distance was predominantly 5–20 m (54%) in matches and <5 m (65%) in training. While head impact location most frequently was at frontal areas, one‐third of all headers in Under‐11 in matches hit temporal, parietal, and occipital parts of the head. Conclusion Heading incidence was low in the youngest age group, whereas (predominantly five) Under‐15 males showed very high heading exposures in training. In assessment and regulation of heading burden, training sessions and individual heading behavior should specifically be addressed. Recommendations for heading the ball in practice should account for individual and age‐related differences.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Mobile Electroencephalography Reveals Differences in Cortical Processing During Exercises With Lower and Higher Cognitive Demands in Preadolescent Children - Becker, Linda; Büchel, Daniel; Lehmann, Tim; Kehne, Miriam; Baumeister, Jochen (Pediatric Exercise Science)
Purpose : The aim of this study was to examine whether cortical activity changes during exercise with increasing cognitive demands in preadolescent children. Method : Twenty healthy children (8.75 [0.91] y) performed one movement game, which was conducted with lower and higher cognitive demands. During a baseline measurement and both exercise conditions, cortical activity was recorded using a 64-channel electroencephalographic system, and heart rate was assessed. Ratings of perceived excertion and perceived cognitive engagement were examined after each condition. To analyze power spectral density in the theta, alpha-1, and alpha-2 frequency bands, an adaptive mixture independent component analysis was used to determine the spatiotemporal sources of cortical activity, and brain components were clustered to identify spatial clusters. Results : One-way repeated-measures analyses of variance revealed significant main effects for condition on theta in the prefrontal cluster, on alpha-1 in the prefrontal, central, bilateral motor, bilateral parieto-occipital, and occipital clusters, and on alpha-2 in the left motor, central, and left parieto-occipital clusters. Compared with the lower cognitive demand exercise, cortical activity was significantly higher in theta power in the prefrontal cluster and in alpha-1 power in the occipital cluster during the higher cognitive demand exercise. Conclusion : The present study shows that exercise complexity seems to influence cortical processing as it increased with increasing cognitive demands.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; Pediatrics; Perinatology and Child Health

A Comparison of the Most Intense Periods (MIPs) During Competitive Matches and Training Over an 8-Week Period in a Male Elite Field Hockey Team - Büchel, Daniel; Döring, Michael; Baumeister, Jochen (Journal of Science in Sport and Exercise)
Abstract Purpose Wearables serve to quantify the on-court activity in intermittent sports such as field hockey (FH). Based on objective data, benchmarks can be determined to tailor training intensity and volume. Next to average and accumulated values, the most intense periods (MIPs) during competitive FH matches are of special interest, since these quantify the peak intensities players experience throughout the intermittent matches. The aim of this study was to retrospectively compare peak intensities between training and competition sessions in a male FH team competing in the first german division. Methods Throughout an 8-week in-season period, 372 individual activity datasets (144 datasets from competitive sessions) were recorded using the Polar Team Pro sensor (Kempele, Finland). MIPs were calculated applying a rolling window approach with predefined window length (1–5 min) and calculated for Total distance, High-Intensity-Running distance (> 16 km/h), Sprinting distance (> 20 km/h) and Acceleration load. Significant differences between training and competition MIPs were analysed through non-parametric statistical tests ( P < 0.05). Results Analyses revealed higher MIPs during competition for all considered outcomes ( P < 0.001). Effect size estimation revealed strongest effects for sprinting distance ( d = 1.89 to d = 1.22) and lowest effect sizes for acceleration load ( d = 0.92 to d = 0.49). Conclusion The present findings demonstrate that peak intensities during training do not reach those experienced during competitive sessions in a male FH team. Training routines such as manipulations of court-dimensions and team sizes might contribute to this discrepancy. Coaches should compare training and competition intensities to recalibrate training routines to optimize athletes’ preparation for competition.
Keywords: Nutrition and Dietetics; Rehabilitation; Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation; Physiology

Alterations of postural control across the menstrual cycle – A systematic review - Pohle, Carina; Becker, Linda; Baumeister, Jochen (Gait & Posture)
Keywords: Rehabilitation; Orthopedics and Sports Medicine; Biophysics

Return to play in elite rugby players after severe knee injuries - Robyn, Aneurin D.; Louw, Quinette A.; Baumeister, Jochen (South African Journal of Physiotherapy)
Background: Medical professionals working in an elite sport environment have the challenging task to balance the athlete’s readiness to return to the playing field after severe injury with other stakeholders’ (coaches, sponsors, teammates) opinions and objectives.Objectives: Our study aimed to evaluate differences in the physical profiles of elite rugby players at return to play (RTP) after a severe knee injury, compared with their pre-injury profiles and matched controls.Method: Before the injury, participants performed four performance tests during their preseason screening. These tests were repeated and compared to baseline once a player was declared fit to play.Results: Significant differences (p ≤ 0.05) were found in the injured players’ group who were slower over 10 m speed, in their decision-making time and the total time of the reactive agility tests at RTP, whilst controls were significantly faster over 10 m and 30 m speed tests. The countermovement jump outcomes showed significant improvement in the uninjured participants (p ≤ 0.05).Conclusion: Our study highlights that injured players’ running speeds and decision-making times are slower after injury. The uninjured players have a positive outcome to training and match stimulus by improving their running speed and lower body explosive power during the season.Clinical implications: Our study provides insight into the RTP profile of elite rugby players, and a novel finding was the decision-making time deficit. This highlights the importance of cognitive training during injury rehabilitation as athletes make numerous decisions in a pressured and uncontrolled environment during a match. Speed training development is recommended as the athletes were slower after severe knee injury.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation

Comparing lab and field agility kinematics in young talented female football players: Implications for ACL injury prevention - Di Paolo, Stefano; Nijmeijer, Eline; Bragonzoni, Laura; Dingshoff, Evelien; Gokeler, Alli; Benjaminse, Anne (European Journal of Sport Science)
Keywords: Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation; General Medicine